Compound-specific stable isotope analyses of fatty acids indicate feeding zones of zooplankton across the water column of a subalpine lake - Pilecky, Matthias; Kämmer, Samuel K; Winter, Katharina; Ptacnikova, Radka; Meador, Travis B; Wassenaar, Leonard I; Fink, Patrick; Kainz, Martin J (Oecologia, 2024)
Spatial and temporal zooplankton feeding dynamics across the water column of lakes are key for understanding site-specific acquisition of diet sources. During this 6-week lake study, we examined stable carbon (δ13C) and nitrogen (δ15N) isotopes and conducted compound-specific fatty acid (FA) stable isotope analysis (CSIA) of edible seston in the epi-, meta-, and hypolimnion, and zooplankton of Lake Lunz, Austria. We predicted that CSIA of essential FA can discern the foraging grounds of zooplankton more accurately than the commonly used bulk stable isotopes. The δ13C and δ15N values of seston from different lake strata were similar, whereas a dual CSIA approach using stable carbon and hydrogen isotopes of FA (δ13CFA and δ2HFA) provided sufficient isotopic difference in essential FA to discern different lake strata-specific diet sources throughout the study period. We present a CSIA model that suggests strata-specific foraging grounds for different zooplankton groups, indicating higher preference of cladocerans for feeding on epilimnetic diet sources, while calanoid copepods retained more hypolimnetic resources. The CSIA approach thus yields strata-specific information on foraging strategies of different zooplankton taxa and provides more details on the spatial and temporal trophodynamics of planktonic food webs than commonly used bulk stable isotopes.
Keywords: jezera; Lakes; Nitrogen Isotopes; Zooplankton; Diet; zvířata; potravní řetězec; Feeding Behavior; Austria; izotopy dusíku; Carbon Isotopes; Compound-specific stable isotopes; GC-IRMS; Trophic ecology; Deuterium; Essential fatty acids; Fatty Acids; izotopy uhlíku; Animals; stravovací zvyklosti; zooplankton; Food Chain; Diel vertical migration; Rakousko; mastné kyseliny; Zooplankton feeding; dieta